"You Don't Need to Time It, You Just Need to See It": Racing in Children's Science - Richard Frazier (Networks: An Online Journal for Teacher Research, 2002)
The work I present here arose from a number of biases, several of which are described [in the introduction]. Prominent among the biases is extensive experience of teaching science with an averred emphasis on activity and inquiry. Along with the perspective of practitioner is the belief that children's ideas in science are worthy of scrutiny. Fascination with the research into children's conceptions and practices was tempered, however, by puzzlement over the actions teachers ought to take. Reflections on the gap between children's science and standard science came while straddling the gap between my perspective as a teacher of children and a researcher into children's ideas. The reflections have been enriched, too, by recent work with preservice elementary teachers in science.